The Effect of Sustainibility Reporting Disclosure and Its Impact on Companies Financial Performance - Enny Hardi; Chairina Chairina (Journal of Wetlands Environmental Management, 2019)
The purpose of this research was to examine empirically the effect of sustainability reporting disclosure on company performance. Sustainability reporting is a report that measures, discloses and shows the responsibility of the company to internal and external parties as an accountability form of organization performance in order to gain continuous development purpose. Sustainability reporting becomes trend and need for companies to disclose economic, environmental, and social performance to stakeholders. Samples used as many as 40 observations were derived from companies that consistently become ISRA (Indonesia Sustainability Reporting Award) nomination and listed in Indonesia Stock Exchange (BEI) during 2016-2017. Sustainability reporting measured by GRI (Global Reporting Initiative) continuous reporting guideline-G4 with 91 indicator items and financial performance measured by Return on Assets (ROA). The analysis method used was Multiple Linear Regression. The results of the research show that Economic Dimension Disclosure (EC) in sustainability reporting has effect on financial performance. Whereas, Environmental Dimension (EN) and Social Dimension (SO) have no effects. The condition indicates that sustainability reporting in short term has not been able to affect companies financial performance.